Current neurochemical and pharmacological aspects of biogenic amines : their function, oxidative deamination, and inhibition - Yu, Peter M.; Tipton, Keith F.; Boulton, A. A. (Alan A.); ScienceDirect eBooks; International Amine Oxidases Workshop 1994 : Saskatoon, Sask.); Trace Amines Symposium 1994 : Saskatoon, Sask.) (Amsterdam ; New York : Elsevier, 1995)
This book contains anonymous-peer-reviewed invited contributions from a joint meeting of the 6th Amine Oxidase Workshop and the 5th Trace Amine Conference, August 1994, Saskatoon, Canada. New developments in both basic and applied studies related to monoamine oxidases (MAO), semicarbazide-sensitive amine oxidase (SSAO) and the trace amines are addressed.
Includes bibliographical references and index.
Online resource; title from publisher's Web site (ScienceDirect, viewed on June 15, 2012).
Elsevier
Keywords: Biogenic amines -- Physiological effect -- Congresses; Biogenic amines -- Metabolism -- Congresses; Monoamine oxidase -- Congresses; Monoamine oxidase -- Inhibitors -- Congresses; Biogenic amines -- Metabolism; Biogenic amines -- Physiological effect; Monoamine oxidase; Monoamine oxidase -- Inhibitors; Electronic books